The Enhancement of Dance Learning Achievement Through the Peer Tutor Learning Model for Grade VIII 1 Students at SMP N 5 Muara Bungo - Asmiwirda, Asmiwirda (The Future of Education Journal, 2023)
Art is one element of culture that has the potential for national development. This type of research is Classroom Action Research (PTK/Classrom Action Research). The results showed that the application of peer tutoring learning can increase children's learning activities and achievements from cycle I to cycle II. Student activity increased from the percentage of 55% in the starting to develop category (BM) in pre-cycle conditions to 67.25% which indicated the category of developing according to expectations (BSH) in cycle I, which then increased again to 81.5% in the very well developed category ( BSB) in cycle II. Classical student learning completeness, namely 20% underdeveloped category (BB) in pre-cycle conditions increased to 35% undeveloped category (BB) in cycle I, and increased to 85% very well developed category (BSB) in cycle II. So from the results above, it can be concluded that optimizing the application of peer tutoring in learning the art of dance is proven to be able to increase the activity and learning achievement of dance for class VIII 1 students of SMP N 5 Muara Bungo in the 2017-2018 academic year.